2016
DOI: 10.1186/s13195-016-0176-z
|View full text |Cite
|
Sign up to set email alerts
|

Mini Mental State Examination and Logical Memory scores for entry into Alzheimer’s disease trials

Abstract: BackgroundSpecific cutoff scores on the Mini Mental State Examination (MMSE) and the Logical Memory (LM) test are used to determine inclusion in Alzheimer’s disease (AD) clinical trials and diagnostic studies. These screening measures have known psychometric limitations, but no study has examined the diagnostic accuracy of the cutoff scores used to determine entry into AD clinical trials and diagnostic studies.MethodsClinicalTrials.gov entries were reviewed for phases II and III active and recruiting AD studie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
104
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(113 citation statements)
references
References 42 publications
2
104
0
3
Order By: Relevance
“…Although MMSE is one of the most widely used tools in the evaluation of cognitive status, there is still a debate about its diagnostic accuracy. Some studies have reported that MMSE lacks diagnostic specificity and has limited diagnostic accuracy, particularly for distinguishing between normal cognition and MCI, and MCI from demential patients with AD (Chapman et al., ) and in measuring the progression of Alzheimer's disease (Clark et al., ). On the other hand, MMSE has been regarded as a good first step in the evaluation of cognitive status and effectively separating those with mild AD from normal aging and MCI (Benson, Slavin, Tran, Petrella, & Doraiswamy, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although MMSE is one of the most widely used tools in the evaluation of cognitive status, there is still a debate about its diagnostic accuracy. Some studies have reported that MMSE lacks diagnostic specificity and has limited diagnostic accuracy, particularly for distinguishing between normal cognition and MCI, and MCI from demential patients with AD (Chapman et al., ) and in measuring the progression of Alzheimer's disease (Clark et al., ). On the other hand, MMSE has been regarded as a good first step in the evaluation of cognitive status and effectively separating those with mild AD from normal aging and MCI (Benson, Slavin, Tran, Petrella, & Doraiswamy, ).…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have reported that MMSE lacks diagnostic specificity and has limited diagnostic accuracy, particularly for distinguishing between normal cognition and MCI, and MCI from demential patients with AD (Chapman et al, 2016) and in measuring the progression of Alzheimer's disease (Clark et al, 1999). On the other hand, MMSE has been regarded as a good first step in the evaluation of cognitive status and effectively separating those with mild AD from normal aging and MCI (Benson, Slavin, Tran, Petrella, & Doraiswamy, 2005 .251 USC B: unstandardized regression coefficient; SC Beta: standardized coefficient; R 2 : squared multiple correlation coefficient; SE: standard errors of the regression coefficients; Sig: two-sided observed significance levels (p) for the t statistics.…”
Section: Discussionmentioning
confidence: 99%
“…Also, since the cut-off points of MMSE might not accurately correlate to the patient's cognitive state, we compared the mean scores before and after therapy and did not group the patients according to the cut-offs [15]. Future studies with the help of other cognitive assessment tools can help to have a more accurate identification of this problem.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies listed in Tables i and iii were not included in meta-analysis due to concern about duplication of subjects. For example, it is probable that a significant proportion of the data report by Chapman et al (2016) is already represented by other studies as it is drawn from the National Alzheimer’s Coordinating Centre (NACC database). Associative Learning and Other categories were not included in meta-analyses due to heterogeneity of measures.…”
Section: Methodsmentioning
confidence: 99%